RoboCup: the evolution of a robotic scientific challenge - Ribeiro, A. Fernando (2005)
The RoboCup is a scientific challenge used to foster research in the robotics areas, which main objective consists in developing a robotic football team able to play against a human team in the year 2050. This paper describes the rules of such a competition, the actual state of the art of robotic football players in the middle size league, and describes the main characteristics to take into account in order to build such type of robots. These aspects are described and analysed in terms of further developments.